2015
DOI: 10.1038/ncomms7565
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunoglobulin transcripts and hypermutation following SHIVAD8 infection and protein-plus-adjuvant immunization

Abstract: Developing predictive animal models to assess how candidate vaccines and infection influence the ontogenies of Envelope (Env)-specific antibodies is critical for the development of an HIV vaccine. Here we use two nonhuman primate models to compare the roles of antigen persistence, diversity and innate immunity. We perform longitudinal analyses of HIV Env-specific B-cell receptor responses to SHIVAD8 infection and Env protein vaccination with eight different adjuvants. A subset of the SHIVAD8-infected animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 70 publications
3
83
0
Order By: Relevance
“…Peripheral blood mononuclear cell, lymph node cell, plasma, and serum separation NHP blood processing was performed as previously reported, 60 and is described in the supplemental Methods.…”
Section: Methods Study Animals Immunizations and Samplingmentioning
confidence: 99%
“…Peripheral blood mononuclear cell, lymph node cell, plasma, and serum separation NHP blood processing was performed as previously reported, 60 and is described in the supplemental Methods.…”
Section: Methods Study Animals Immunizations and Samplingmentioning
confidence: 99%
“…In this study, we showed that the neutralization-resistant R5 tropic SHIV-MK38#818 molecular clone derived from SHIV-KS661 can cause stably persistent infection with high viral load via intrarectal inoculation despite the immune responses that occurred in the host. Currently, SHIV AD8 , categorized as a tier 2 neutralization-resistant phenotype, is widely used as a SHIV challenge virus for a variety of vaccine developments (Nishimura et al, 2010;Shingai et al, 2012Shingai et al, 2013;Gardner et al, 2015;Francica et al, 2015). However, use of SHIV AD8 as the only challenge virus is very risky for precise evaluation in vaccine candidates and anti-HIV-1 neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Human antibody sequences were analyzed using IMGT/V-QUEST (http://www.imgt.org/). Rhesus antibody sequences were analyzed using IgBLAST (47) to align them against a collection of rhesus germ line V genes (48,49) and to calculate hypermutation frequencies. The rhesus germ line V gene that gave the lowest hypermutation frequency for each query sequence was assigned and reported.…”
Section: Methodsmentioning
confidence: 99%